Intermediate Method : Flute or Piccolo - SKORNICKA, J.E and A.C Petersen (Rubank Inc., 1939)
Good tone is necessary-in order that one's playing be pleasing to the listener as wellas the player. Good tone can be produced only when the instrument is in good playing condition, equipped with the correct type of mouthpiece and played with the correct embouchure.